The couple at the table : a novel - Hannah, Sophie, 1971- (Hannah, Sophie, 1971- Zailer and Waterhouse mystery, 2022)
"Jane and William are enjoying their honeymoon at an exclusive couples-only resort ... until Jane receives a chilling note warning her to "Beware of the couple at the table nearest to yours." At dinner that night, five other couples are present, and none of their tables is any nearer or farther away than any of the others. It's almost as if someone has set the scene in order to make the warning note meaningless--but why would anyone do that? Jane has no idea. But someone in this dining room will be dead before breakfast, and all the evidence will suggest that no one there that night could have possibly committed the crime"--